Impact of percutaneous revascularization on exercise hemodynamics in patients with stable coronary disease - Cook,CM; Ahmad,Y; Howard,JP; Shun-Shin,MJ; Sethi,A; Clesham,GJ; Tang,KH; Nijjer,SS; Kelly,PA; Davies,JR; Malik,IS; Kaprielian,R; et al. (Journal of the American College of Cardiology, 2018)
BACKGROUND: Recently, the therapeutic benefits of percutaneous coronary intervention (PCI) have been challenged in patients with stable coronary artery disease (SCD). OBJECTIVES: The authors examined the impact of PCI on exercise responses in the coronary circulation, the microcirculation, and systemic hemodynamics in patients with SCD. METHODS: A total of 21 patients (mean age 60.3 ± 8.4 years) with SCD and single-vessel coronary stenosis underwent cardiac catheterization. Pre-PCI, patients exercised on a supine ergometer until rate-limiting angina or exhaustion. Simultaneous trans-stenotic coronary pressure-flow measurements were made throughout exercise. Post-PCI, this process was repeated. Physiological parameters, rate-limiting symptoms, and exercise performance were compared between pre-PCI and post-PCI exercise cycles. RESULTS: PCI reduced ischemia as documented by fractional flow reserve value (pre-PCI 0.59 ± 0.18 to post-PCI 0.91 ± 0.07), instantaneous wave-free ratio value (pre-PCI 0.61 ± 0.27 to post-PCI 0.96 ± 0.05) and coronary flow reserve value (pre-PCI 1.7 ± 0.7 to post-PCI 3.1 ± 1.0; p < 0.001 for all). PCI increased peak-exercise average peak coronary flow velocity (p < 0.0001), coronary perfusion pressure (distal coronary pressure; p < 0.0001), systolic blood pressure (p = 0.01), accelerating wave energy (p < 0.001), and myocardial workload (rate-pressure product; p < 0.01). These changes observed immediately following PCI resulted from the abolition of stenosis resistance (p < 0.0001). PCI was also associated with an immediate improvement in exercise time (+67 s; 95% confidence interval: 31 to 102 s; p < 0.0001) and a reduction in rate-limiting angina symptoms (81% reduction in rate-limiting angina symptoms post-PCI; p < 0.001). CONCLUSIONS: In patients with SCD and severe single-vessel stenosis, objective physiological